Conservative Management of Uterovesical Fistula Following Primary Caesarean Section - Bastakoti, Rashmi; Saha, Rachana (Journal of Kathmandu Medical College, 2014)
Uterovesical fistula is an abnormal communication between uterine cavity and the bladder. It is a rare type of fistula accounting for four percent of all cases of urogenital fistula. However the incidence of uterovesical fistula has been rising due to increasing incidence of lower segment caesarean section. Uterovesical fistula is seen more after repeated caesarean section rather than primary section. This is a case report of a primipara with uterovesical fistula following primary emergency Caesarean section on her 12th postoperative day for foetal distress. She was managed conservatively using IV antibiotics and catheterization for six weeks. DOI: http://dx.doi.org/10.3126/jkmc.v2i4.11799 Journal of Kathmandu Medical College Vol. 2, No. 4, Issue 6, Oct.-Dec., 2013 Page: 211-213